Case report: Sarcocystis speeri, Aspergillus fumigatus, and novel Treponema sp. infections in an adult Atlantic spotted dolphin (Stenella frontalis) - Balik, Sarah Emily; Ossiboff, Robert James; Stacy, Nicole Indra; Wellehan, James F. X.; Huguet, Elodie E.; Gallastegui, Aitor; Childress, April L.; Baldrica, Brittany E.; Dolan, Brittany A.; Adler, Laurie E.; Walsh, Michael Thomas (Frontiers in Veterinary Science, 2023)
A complete postmortem examination, including a computed tomography scan “virtopsy” (virtual necropsy), gross necropsy, cytology, histology, and molecular diagnostics were performed to investigate the cause of death of a deceased adult male Atlantic spotted dolphin (Stenella frontalis) that stranded on Pensacola Beach, Florida, USA in February 2020. Significant findings included chronic inflammation of the meninges, brain, and spinal cord with intralesional protozoa (identified as Sarcocystis speeri via 18S rRNA and ITS-1 sequences), suppurative fungal tracheitis and bronchopneumonia (identified as Aspergillus fumigatus via ITS-2 gene sequence) and ulcerative bacterial glossitis (associated with a novel Treponema species, Candidatus Treponema stenella, identified via 23S rRNA gene sequence). This is the first reported case of S. speeri in a marine mammal. Little is understood about the epidemiology of S. speeri, including the identity of its intermediate hosts. The findings of this case suggest that S. frontalis may be a capable aberrant host and experience morbidity and mortality from this parasite. It is suspected that the novel Treponema and Aspergillus fumigatus infections were opportunistic or secondary to immunosuppression, either due to S. speeri infection or other co-morbidities.